The invention of death in Ancient Egypt: Christian Eurocentrism in interpretations of Egyptian funerary beliefs - Canto Núñez, Pedro Hugo (Romanitas - Revista de Estudos Grecolatinos, 2026)
Review of: NYORD, Rune. Yearning for Immortality: The European Invention of the Ancient Egyptian Afterlife. Chicago: University of Chicago Press, 2025. 316 p.
Keywords: Egyptology; Historiography; Egyptian Funerary Religion